Climate change will trade-off summer and winter energy burdens - Camilo Toruno; Andrew Schallwig; Ritvik Jain; Claire McKenna; Parth Vaishnav; Seth Guikema; Michael T Craig (Environmental Research: Energy)
High energy burdens challenge nearly a quarter of U.S. households, a fraction which could increase under climate change due to its impacts on space heating and cooling usage. Using detailed building models, physics-based building simulations, and downscaled meteorological data, we quantify seasonal and annual household energy costs for nearly 6600 low-income households across 25 U.S. cities under historic and future climates. Climate change will, on average, reduce households’ median annual energy costs in heating-dominated cities by 4%–7%, and increase them 1%–6% in hot–humid cities. But climate change will increase summer energy costs for most households and cities, with average households’ total energy costs in each city seeing summer increases of 2%–10%. Furthermore, buildings with characteristics commonly associated with low-income households (e.g. high air infiltration rates) are particularly vulnerable to rising summer energy costs under climate change. Absent increasing household wages or support, our results suggest climate change will exacerbate annual energy burdens across the southern U.S., and increase summer energy burdens while alleviating winter energy burdens in most U.S. cities.